Faktor yang Berhubungan dengan Kejadian Hipertensi pada Dewasa Muda di Puskesmas Toddopuli Makassar - Lativatul Isyaroh; Nurmiati Muchlis; Nurul Ulfah Mutthalib (Window of Public Health Journal, 2026)
Hypertension is a condition of increased blood pressure in the blood vessels, characterized by systolic pressure ≥140 mmHg and/or diastolic pressure ≥90 mmHg. This study aims to determine the factors associated with the incidence of hypertension in young adults at the Toddopuli Community Health Center, Makassar. The type of research used is quantitative research with a cross-sectional approach. The population in this study amounted to 169 respondents, with a sample size of 117 respondents determined using the Lemeshow formula. Data collection was carried out using a questionnaire. Data analysis included univariate and bivariate analysis, which was presented in tabular form and interpreted narratively. The results showed that there was a significant relationship between dietary patterns (p < 0.001), smoking status (p < 0.001), sleep patterns (p = 0.001), stress levels (p < 0.001), and knowledge levels (p < 0.001) with the incidence of hypertension in young adults. It is hoped that young adults will pay more attention to the risk factors for hypertension as an effort to prevent and control the disease.